Recent changes in summer distribution and numbers of migratory caribou on the southern Hudson Bay coast - Abraham, Kenneth F.; Pond, Bruce A.; Tully, Susan M.; Trim, Vicki; Hedman, Daryll; Chenier, Chris; Racey, Gerald D. (Rangifer, 2012)
The status of migratory woodland caribou inhabiting the coastal region in southern Hudson Bay is dynamic. The Pen Islands Herd within that region was defined in the 1990s, but opportunistic observations between 1999 and 2007 suggested that its status had significantly changed since the late 1980s and early 1990s. We undertook systematic surveys from the Hayes River, MB, to the Lakitusaki River, ON, in 2008 and 2009 to determine current distribution and minimum numbers of woodland caribou on the southern Hudson Bay coast from the Hayes River, Manitoba, to the Lakitusaki River, Ontario. We documented a significant change in summer distribution during the historical peak aggregation period (7-15 July) compared to the 1990s. In 2008 and 2009, respectively, we tallied 3529 and 3304 animals; however, fewer than 180 caribou were observed each year in the Pen Islands Herd’s former summer range where over 10 798 caribou were observed during a systematic survey in 1994. Over 80% of caribou were in the Cape Henrietta Maria area of Ontario. Calf proportions in herds varied from 8% of animals in the west to 20% in the east. Our 2008 and 2009 systematic surveys were focused on the immediate coast, but one exploratory flight inland suggested that more caribou may be inland than had been observed in the 1980s-1990s. The causes of change in the numbers and distribution in the coastal Hudson Bay Lowlands and the association of current caribou with the formerly large Pen Islands Herd may be difficult to determine because of gaps in monitoring, but satellite telemetry, genetic sampling, remote sensing, habitat analysis, and aboriginal knowledge are all being used to pursue answers.